Depression, anxiety, psychotropic drugs, and acute myocardial infarction: large prospective study of United Kingdom women - Parkin, L; Balkwill, A; Green, J; Reeves, G; Beral, V; Floud, S (Cambridge University Press, 2021)
Background: Reported associations between depression and myocardial infarction in some studies might be explained by use of psychotropic drugs, residual confounding, and/or reverse causation (whereby heart disease precedes depression). We investigated these hypotheses in a large prospective study of UK women with no previous vascular disease.